2019
DOI: 10.4000/anglophonia.2005
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of creaky voice use in read speech by native-French and native-English speakers in tandem: a pilot study

Abstract: Non modale (non neutre), la voix craquée se manifeste aux niveaux segmental et suprasegmental des langues. Elle revêt également des fonctions pragmatiques, stylistiques, sociolinguistiques et extralinguistiques. Si sa prévalence est attestée en anglais américain, elle est plus rare en français. Lors de lectures en tandem linguistique entre étudiant.e.s anglophones et francophones, la voix craquée de chaque langue parlée évolue-t-elle ? Pour cette étude pilote par 9 paires –un.e anglophone et un.e francophone–,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…This is perhaps because the use of creaky voice is often seen as an individual characteristic related to, for example, social status rather than as a feature of a language [39,40]. The few studies that have investigated creakiness in L2 focus on how well speakers can avoid creakiness in the target language [20,21]. Our results, however, suggest that using creaky voice in L2 Finnish can affect the perception of fluency and proficiency positively.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This is perhaps because the use of creaky voice is often seen as an individual characteristic related to, for example, social status rather than as a feature of a language [39,40]. The few studies that have investigated creakiness in L2 focus on how well speakers can avoid creakiness in the target language [20,21]. Our results, however, suggest that using creaky voice in L2 Finnish can affect the perception of fluency and proficiency positively.…”
Section: Discussionmentioning
confidence: 61%
“…Language learners may thus be perceived as more native-like, if they manage to use creaky voice appropriately, while the absence of creaky voice can make the L2 speaker sound less fluent. However, studies on L2 and the use of creaky voice indicate that it is easier for a language learner to reduce creakiness than include it in speech [20,21], perhaps because creaky voice, in relation to modal voice, can be considered as an individual characteristic. Pillot-Loiseau et al [20] found that English learners of French -a language where creaky voice is considered unusual -reduced the use of creaky voice when speaking French compared to their L1 English, although they still used more creaky voice than native speakers of French.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceptually, the voice quality is perceived as a comparably sudden decrease in pitch (Kreiman, 1982). Since this voice quality has been shown to undergo accommodation effects, their occurrences were excluded from the analysis (Pillot-Loiseau et al, 2019). In total 1237 prenuclear pitch accents were analyzed, 663 produced by the HP speakers and 574 produced by the LP speakers.…”
Section: Pitch Range On Prenuclear Accentsmentioning
confidence: 99%
“…L'étude des personnes bilingues et des différences de voix selon leurs langues constitue un cas particulièrement éclairant pour étudier la composante culturelle et non physiologique des voix humaines (Pillot-Loiseau et al, 2019).…”
unclassified